Fuzzy modeling of the effects of the use of mineral and organic fertilizers on the productivity of second crop corn - Godinho, Emmanuel Zullo; Caneppele, Fernando de Lima; Gasparotto, Helio Vagner; Luciano, Leonardo Pereira de Almeida (Revista Brasileira de Engenharia de Biossistemas, 2022)
A high productivity in a culture mainly the corn it is associated with many factors, like technological application, integrated management of plagues and diseases, soil fertility, primarily for the disponibility in soil nutrients. The present study has a its objective to analyze statistically the corn productivity with a different dosage of the 5-10-10 mineral fertilizers and organic bovine composting and develop a logic-based system Fuzzy of the agronomic parameters. The experiment measured corn productivity in five different dosages of mineral and organic fertilizers, being developed in the field at Colégio Agrícola de Toledo (CAET), Toledo/PR, Brazil. The results showed that a specific range of fertilizer dosages (mineral and organic) can increase corn productivity in the second crop. With the Fuzzy model developed, it was possible to verify the importance of the use of optimization tools that can assist in the analysis of experimental data and allow performing simulations capable of inferring points that have not been determined experimentally in the field.